Research trends and hotspots regarding treatment of obstructive sleep apnea - Yang, Xia; Wen, Yi; Xie, Shiqi; Chen, Jinglan; Liu, Yue; Zhou, Jianrong (Frontiers in Neurology, 2023)
Background: Obstructive sleep apnea (OSA) is a type of sleep-disordered breathing disease, with high prevalence and multiple complications. It seriously affects patients' quality of life and even threatens their lives. Early and effective treatment can significantly improve patients' health conditions.Objective: In this study, the main treatment methods, research hotspots and trends of obstructive sleep apnea were summarized through bibliometric and visualization analysis.From the Web of Science Core Collection database, articles on the treatment of OSA from 1999 to 2022 were obtained. CiteSpace and VOSviewer were comprehensively used to visualization of journals, co-authorship of countries, institutions and authors, co-citation of references, keywords cluster and burst.Results: A total of 2874 publications were obtained, of which 2584 were concerned adults and 290 about children. In adults' research, Sleep and Breathing is the most published journal (280,10.84%), the largest number of publications come from the United States (636,24.61%) and the University of Sydney (88,3.41%), and Pepin JL is the most published author (48,18.58%). In children's studies, International Journal of Pediatric Otorhinolaryngology is the most published journal (41,14.14%), the maximum number of publications were also from the United States (123,42.41%), with the University of Pennsylvania (20,6.90%) and Marcus CL (15,5.17%) being the most published institutions and authors. High-frequency keywords for adults' researches include positive airway pressure, oral appliance, surgery and positional therapy. On these basis, children's studies also focus on myofunctional therapy, rapid maxillary expansion and hypoglossal nerve Stimulation.Over the past two decades, research in the field of OSA therapeutics has experienced significant growth in depth and breadth. The author cooperation network has already established a solid foundation, while there is potential for further strengthening the cooperation network between countries and institutions. Currently, positive airway pressure and surgery are the primary treatments